2018
DOI: 10.1108/imp-12-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marketing mix and retailer-perceived brand equity

Abstract: Purpose A huge investment launching the marketing program is made by the manufacturers to establish brand loyalty with retailers and other supply chain partners; however, what is the impact of these efforts on retailer-perceived brand equity (RPBE) is scarcely investigated in a business-to-business (B2B) context. The purpose of this paper is to investigate the impact of Nu Green – a brand of tea as a manufacturer’s marketing efforts on RPBE. Design/methodology/approach Based on the positivist paradigm, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…To also gain brand loyalty, this study found that all Woolworths' marketing offerings are significantly contributing as did Anselmsson et al. (2017) and Efanny et al. (2018).…”
Section: Discussionmentioning
confidence: 70%
“…To also gain brand loyalty, this study found that all Woolworths' marketing offerings are significantly contributing as did Anselmsson et al. (2017) and Efanny et al. (2018).…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, other stimuli considered in the CB model are economy, politics, technology, and culture. [8] expressed that marketing mix (price, product, promotion, and place) is an influential factor in brand consciousness and consumer satisfaction. Similarly, [9] confirmed that the marketing mix affected the quality expectation of a product and trust in the brand that leads to purchasing decisions.…”
Section: Marketing Stimuli and Product Innovationmentioning
confidence: 99%
“…Perceived advertisement spends has an effect on perceived quality, brand awareness and brand image (Villarejo-Ramos & Sánchez-Franco, 2005). Push and pull promotions have a significant effect on the dealer brand equity (Efanny, Haryanto, Kahif, & Vidyanto, 2018). Distribution-promotion has an effect on perceived quality, and higher level promotion generates a higher level brand quality signal (Chattopadhyay et al, 2010).…”
Section: Service Marketing MIX Elementsmentioning
confidence: 99%